2018
DOI: 10.3889/oamjms.2018.394
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Omalizumab in Asthma as a Major Compliance Factor: 10-Year Follow Up

Abstract: BACKGROUND:There is a lack of data related to real life, long-term safety, tolerability and compliance of omalizumab treatment in asthma patients beyond 6 years.AIM:Study aimed to assess safety, tolerability, compliance and all reasons for treatment discontinuation during 10 years on omalizumab.SUBJECT AND METHODS:This is a retrospective, observational study of uncontrolled asthma patients receiving omalizumab for the last 10 years. All data were collected from patients’ files (demographics, adverse events, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…General characteristics of the twelve included studies that reported on study‐emergent solid epithelial cancer are summarized in Tables and . Additional details can be found in Appendix .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…General characteristics of the twelve included studies that reported on study‐emergent solid epithelial cancer are summarized in Tables and . Additional details can be found in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these studies included a total of 11 758 participants and encompassed three study types. Three were RCTs, one was a comparative observational study (prospective cohort), and eight were non‐comparative observational studies . Their publication dates ranged from 2002 to 2018; however, 75% were published in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations